A compatibility testing platform for android multimedia applications - Liu, Chien-Hung (Multimedia tools and applications, 2019)
Along with the widespread use of smartphones, Android has become one of the major platforms for multimedia applications (apps). However, due to the fast evolution of Android operating system and the fragmentation of Android devices, it becomes important for an Android multimedia app to be tested on different devices to ensure that the app is compatible with and run well on any of the devices so as to provide consistent user experiences. This paper presents a cloud testing platform (CTP) that allows Android multimedia apps to be tested automatically against a scalable number of physical devices in parallel. Particularly, CTP provides five types of testing to ensure the compatibility of apps from different perspectives, including GUI testing, acceptance testing, stress testing, crash testing, and installation/uninstallation testing. Further, to facilitate identifying the bugs of apps, in addition to test results, CTP also provides the video, screenshots, and performance data corresponding to the tests. Moreover, CTP can also generate a GUI state diagram that can be used to analyze app’s behavior and is helpful for crash diagnosis and debugging. The case study shows that CTP can be effective in ensuring the compatibility of Android multimedia apps while saving test time and effort.